1996
DOI: 10.1063/1.117123
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the spatially resolved field emission characteristics and the raman spectra of a nanocrystalline diamond cold cathode

Abstract: Spatially resolved electron field emission measurements from a nanocrystalline diamond film grown by plasma-enhanced chemical transport deposition have been obtained using a scanning probe apparatus with micrometer resolution. Macroscopic regions with a high emission site density, and turn-on fields below 3 V/μm, comprised approximately 1/2 of the total sample area. The emitting and the nonemitting regions of the specimen are differentiated distinctly by Raman spectra and subtly by morphologies. Both areas are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(37 citation statements)
references
References 2 publications
0
37
0
Order By: Relevance
“…[1][2][3][4] Initial interest was stimulated by the prospect of electron emission at very low electric fields due to the low electron affinity of the carbon in the diamond form when terminated with hydrogen: the diamond surface, in fact, has a negative electron affinity ͑NEA͒. Various carbon based cold cathodes including diamond, 5 nanodiamond, 6 diamondlike carbon ͑DLC͒ and tetrahedral amorphous carbon, 7,8 carbon nanotubes, 9,10 and nanoclustered carbon [11][12][13][14] have all been shown to emit electrons at reasonably low electric fields. The ease of emission from widely different carbon materials suggests that NEA is not a prerequisite and may be a bonus feature.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Initial interest was stimulated by the prospect of electron emission at very low electric fields due to the low electron affinity of the carbon in the diamond form when terminated with hydrogen: the diamond surface, in fact, has a negative electron affinity ͑NEA͒. Various carbon based cold cathodes including diamond, 5 nanodiamond, 6 diamondlike carbon ͑DLC͒ and tetrahedral amorphous carbon, 7,8 carbon nanotubes, 9,10 and nanoclustered carbon [11][12][13][14] have all been shown to emit electrons at reasonably low electric fields. The ease of emission from widely different carbon materials suggests that NEA is not a prerequisite and may be a bonus feature.…”
Section: Introductionmentioning
confidence: 99%
“…1 NCD films with high field-emission (FE) efficacy have been produced using various deposition processes. [2][3][4][5] Composition and bonding structure both influence FE efficacy of an NCD film. NCD films are composed of diamond crystallites and sp 2 -bonded nondiamond carbon.…”
Section: Introductionmentioning
confidence: 99%
“…1 A microscopic analysis of the FE of NCD films revealed that electrons were ejected from defective diamond crystallites with disordered sp 2 carbon rather than from the perfect diamond or graphite phase. 2 The ratio of the intensity of the D-band around 1350 cm À1 to that of the G-band around 1550 cm À1 (I D /I G ) in the Raman spectra has been adopted to describe the macroscopic bonding structure of diamond films, 6,7 and has been correlated with the FE properties of such films. 4 High-efficiency electron emission has been observed from the NCD films with high I D /I G ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Effective field electron emission was observed for different types of carbon objects including chemical vapor deposition CVD diamond films [1,2], diamond-like carbon films [3], nanotubes and graphene films, etc. [4,5].…”
Section: Introductionmentioning
confidence: 99%